Expression of Fas, FasL, caspase-8 and other factors of the extrinsic apoptotic pathway during the onset of interdigital tissue elimination - Svandova, E Budisova; Vesela, B; Lesot, H; Poliard, A; Matalova, E (Histochemistry and cell biology, 2017)
Elimination of the interdigital web is considered to be the classical model for assessing apoptosis. So far, most of the molecules described in the process have been connected to the intrinsic (mitochondrial) pathway. The extrinsic (receptor mediated) apoptotic pathway has been rather neglected, although it is important in development, immunomodulation and cancer therapy. This work aimed to investigate factors of the extrinsic apoptotic machinery during interdigital regression with a focus on three crucial initiators: Fas, Fas ligand and caspase-8. Immunofluorescent analysis of mouse forelimb histological sections revealed abundant expression of these molecules prior to digit separation. Subsequent PCR Array analyses indicated the expression of several markers engaged in the extrinsic pathway. Between embryonic days 11 and 13, statistically significant increases in the expression of Fas and caspase-8 were observed, along with other molecules involved in the extrinsic apoptotic pathway such as Dapk1, Traf3, Tnsf12, Tnfrsf1A and Ripk1. These results demonstrate for the first time the presence of extrinsic apoptotic components in mouse limb development and indicate novel candidates in the molecular network accompanying the regression of interdigital tissue during digitalisation.
Keywords: přední končetina; Fas Ligand Protein; Forelimb development; myši; Animals; Interdigital; Extrinsic apoptotic factors; fas Receptor; Forelimb; Fas pathway; Mitochondria; myši inbrední C57BL; mitochondrie; apoptóza; Caspase 8; Mice; zvířata; Mice, Inbred C57BL; ligand Fas; kaspasa 8; Apoptosis; antigeny CD95